Overview of voltage control and potential applications of secondary voltage regulations in malaysia tenaga nasional berhad grid system - Abdullah S.K.B.S.; Nik Yusuf N.S.B.; Mohd Nor D.B.; Musirin I.B.; Abidin I.B.Z. (2023)
Effective and efficient voltage and reactive power control has become increasingly important due to higher transmission grid utilization and optimization of resources. With numerous voltage control devices and reactive power resources within the transmission system and constantly varying system conditions, timely coordination for use these devices is very necessary. A Coordinated Voltage Control approach that consists of primary voltage control (PVR), secondary voltage control (SVR) and tertiary voltage control (TVR) is the most effective solutions for reactive power and voltage control. In TNB power system, coordinated voltage control system yet to be implemented, but believes that improvement in the approach and methods to performing secondary voltage controls are desirable since it could enhance system performance in terms of reliability and security as well as system losses. A simulation studies has been carried out by TNB Research (a research arm and wholly owned subsidiary of TNB) to determine the feasibility of applying Coordinated Voltage Control (CVC) in TNB's Transmission network from the perspective of system reliability and security as well as economic operation. Form studies conducted, it is clear that implementation of CVC system can bring great potential and benefits to TNB. Immediate benefits can be in the form of loss reduction, better voltage profile and control and effective utilization of reactive resources.